CASE STUDY ON ATTITUDE AND BEHAVIOR OF SCHOOL LUNCH OFFICIALS REGARDING UTILIZATION OF LOCAL PRODUCE -FOCUSING ON THE DIFFERENCE OF OCCUPATION - Tokuhiro, Chie; Shimada, Ikuko; Numata, Satoshi; Kitamura, Kazuko (PEOPLE: International Journal of Social Sciences, 2020)
This study was conducted in January 2010 to identify influential factors for utilization of local produce in school lunch services and factor-correlations in terms of employment types and item types and to review the evaluation index for shokuiku. The research participants were 56 nutrition teachers, 91 school principals, and 23 school lunch directors. The study revealed that school lunch staff had high awareness and behavioral motivation for using local ingredients. School lunch directors were concerned about managerial aspects such as “high price” and “not enough variety and quantity” for making lunches with local ingredients only. The principals expressed high opinion on educational or administrative advantages of using local ingredients in “increased number of local cuisine in the menu” and “securing food safety” but showed low awareness on problems related to using local produce to cook for entire student body such as “longer cooking time” and “not enough providers.” Correlation between questionnaire items revealed that there was a strong positive relation between items emphasizing advantages of using local produce. The results showed that using local produce for providing school lunches could induce changes in behaviors, such as frequenting local produce markets, and it is considered to become a good evaluation index for developing shokuiku.